Field reconnaissance on seismic performance of RC buildings after the January 24, 2020 Elazig-Sivrice earthquake - Yurdakul, Özgür; Duran, Burak; Tunaboyu, Onur; Avsar, Ozgur (Springer, 2021)
A moderate earthquake with a magnitudeM(w)of 6.8 occurred in the Sivrice district of Elazig Province in Eastern Turkey on January 24th, 2020. The mainshock and long-term aftershocks gave rise to considerable structural damage and affected the local society. Remarkable property loss took place due to building damages and collapses. The reasons for the losses and structural damages are investigated by the post-earthquake field observations. The importance of earthquake-resistant design principles and applications outlined in the current and former seismic codes is verified through the field reconnaissance. To this end, the seismic damage observed after the Elazig-Sivrice Earthquake in the non-structural and structural elements of the RC structures is reported. The conflict between the code requirements and actual conditions of construction practices is also established. The seismic vulnerability of substandard RC buildings is quantified in association with the structural weaknesses and deficiencies observed in the earthquake-affected region. The reasons behind the unexpectedly extensive damage at the local and global level under such a moderate earthquake are based on the vulnerability of substandard buildings resulting from structural deficiencies, poor material qualities, and lack of control mechanism during construction.
Keywords: field investigation; reinforced concrete; building damage; structural deficiency; reconnaissance